Twin-resonance-coupling and high sensitivity sensing characteristics of a selectively fluid-filled microstructured optical fiber - Luo, Mingming (2014)
A twin-resonance-coupling phenomenon and the sensing characteristics of a selectively fluid-filled microstructured optical fiber (SFMOF) are proposed and demonstrated. The SFMOF is realized by selectively infiltrating refractive index fluid into a single air hole located at the second ring near the core of the MOF. Twin-resonance dips are observed in the transmission spectrum. Theoretical and experimental investigations reveal that the twin-resonance dips both result from the coupling between LPC01 silica core mode and LPL01 liquid rod mode. Their sensitivities strongly depend on the dispersion curves of the silica and fluid material. Sensitivities of 290 nm/°C (739,796 nm/RIU) and 591.84 nm/N (701.2 pm/µɛ) are achieved, which are the highest for a SFMOF-based device to date, to our best knowledge. Furthermore, the twin-resonance dips appear to shift in the opposite directions with changes in temperature or axial strain, providing a method to achieve two- or multi-parameter measurement in such a compact structure.